PLAY THERAPY IN FORMING THE PSYCHOLOGY OF BROKEN HOME CHILDREN - Ritonga, Ristra Sandra; Munisa, Munisa; Hendrawan, Jodi (Proceeding International Conference of Science Technology and Social Humanities, 2022)
The term broken home child can be interpreted as a child who has a family that is not harmonious and even a family that has been destroyed or whose parents are separated. With problems like this, the child's psychological condition will be disturbed, such as the child will be more moody or even the child will be more aggressive in carrying out daily life. This will be a problem that must be resolved so as not to traumatize the child in the future. With a game-based therapy design or playtherapy using sandbox media and the help of several toys as objects, it is hoped that it can help the psychology of children in borken home families.